PENGARUH KETERIKATAN KERJA, PERSEPSI DUKUNGAN ORGANISASIONAL DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION KARYAWAN MUJI MOTOR - Bitha, Sella; Ardana, I Komang (E-Jurnal Manajemen; Vol 6 No 2 (2017), 2017)
This study aimed to examine the effect of job embeddedness to the labor turnover intention, to test the effect of perceived organizational support to the turnover intention, and to examine the influence of organizational commitment to turnover intention. This research was conducted on Muji Motor which is located in Jalan Trengguli Gang XXII No.5 Denpasar. The number of respondents that used in this study was 108 respondents, all employees of Muji Motor using saturated sample. The analysis technique used in this research is multiple linear regression analysis. The results of this study prove that the job embeddedness of the work has a significant negative effect on turnover intention in Muji Motor, perceived organizational support has a significant negative effect on turnover intention in Muji Motor, and organizational commitment had a significant negative effect on turnover intention in Muji Motor.
Keywords: job embeddedness, perceived organizational support, organizational commitment, turnover intention